2SPD-023 Interest in consignment inventory management of articular prostheses at a university hospital. (March 2019) - Enneffah, W; El Wartiti, MA; Cheikh, A; Abouatia, M; El Ouadghiri, B; Bennana, A; Taoufik, J; Lamsaouri, J
Abstract : Background: The joint prostheses occupy a very important place in the therapeutic arsenal of our establishment, in the part of the number of prostheses that are implemented per year and secondly, by the colossal budget for their supply. Therefore, their circuit from acquisition to use, must be perfectly mastered by hospital pharmacists. Purpose: To highlight the advantages of the Consignment Inventory Management (CIM) of joint prostheses in hospitals Material and methods: In order to demonstrate the organisational interest of the understanding of documents as well as the economic interest that present the CIM of joint prostheses, we have analysed the circuit of articular prostheses at our hospital since their acquisition until their implantation in the patient. Results: The choice of prostheses component's size depends on the anatomical and physiological conditions and also on the age and activity of the future operated patient. As a result, the conventional acquisition of different sizes of each prostheses component has become obsolete. The CIM, which consists in making available, for a contractually defined period, different sizes of the same prosthesis components (which remain the property of the supplier until their use in the patient) is an excellent alternative. This mode of replenishment at the request of the consumed size allowed a better control of availability, expiry dates and traceability, At the economic level, it allowed us to save about €1.7 million per year (on an overall joint prostheses annual budget of €9 million) compared to the classic supply. Conclusion: The CIM based on the automatic replenishment of the consumed parts, combined with controlled traceability, helped the optimisation of expenses, avoiding breaks and ensuring the proper monitoring of these implantable medical devices at our hospital. References and/or acknowledgements: None. No conflict of interest.